Entendiendo la Cultura de 4-H - Marilyn Norman; Joy C. Jordan (EDIS)
4HS-FS101.1-Spn, a 3-page illustrated fact sheet by Marilyn N. Norman and Joy C. Jordan, is part of the 4-H 101 Fact Sheets series.  It is the Spanish language version of 4HS-FS101.1: Understanding 4-H Culture. It describes what 4-H is, the colors, pledge, motto, slogan, name, and emblem. Published by the Florida 4-H Program, July 2009.